Makna Ceng Beng Dalam Perspektif Buddha Dharma - Lalita Vistari SWD (Jurnal Pelita Dharma, 2014)
For the culture of the Chinese community there are two prayers are intended for families who have died in the year, namely : prayer known 3 months Ceng Beng , and prayers in the month 7 (Cit Gwee) known Cioko or Chau Tu . The difference of the second prayer is as follows : Ceng Beng prayer is prayer that is intended for families who have died are still recognizable , while prayer Cit Gwee or more Cioko aims addressed to families who have forgotten (creatures abandoned) by relatives , [hat happens because their family had died all (generation runs) and their families have left the religion of their ancestors , who did not embrace the new religion emphasizes devotion to the ancestors . Prayer Ceng Beng , Cit Cioko Gwee or is relevant to the ceremony in Buddhism , namely Pattidana (ceremony merits).